The Role of Augmented Reality in Online Purchasing Decisions of Beauty Products on the E-commerce Platform Shopee - Lusianingrum, Farah Putri Wenang; Purbohastuti, Arum Wahyuni; Widikusyanto, Muhammad Johan (Universitas Sultan Ageng Tirtayasa, 2025)
The proliferation of augmented reality (AR) in the commercial sector remains constrained in terms of its psychological effects on online purchase behavior. The main aim of the research is to examine the influence of augmented reality on purchasing behavior for cosmetic goods on the Shopee platform based S-O-R theory. The online research study gathered comprehensive data from 200 participants. Purposive sampling selected the respondents. In this study, the analytical instrument used for data processing is Smart PLS. The S-O-R theoretical framework validated and corroborated all hypotheses. The interactivity and vividness of augmented reality significantly improve the user experience for cosmetic goods buyers on Shopee. Moreover, augmented reality interaction and vividness promote an increase in online purchase intent among customers of cosmetic products on Shopee. Furthermore, user experience and online buying intentions effectively drive consumers to make online purchasing decisions for cosmetic products on Shopee.